2011
DOI: 10.1177/1460458211405004
|View full text |Cite
|
Sign up to set email alerts
|

Applying Semantic Web technologies to improve the retrieval, credibility and use of health-related web resources

Abstract: The number of health-related websites is increasing day-by-day; however, their quality is variable and difficult to assess. Various "trust marks" and filtering portals have been created in order to assist consumers in retrieving quality medical information. Consumers are using search engines as the main tool to get health information; however, the major problem is that the meaning of the web content is not machine-readable in the sense that computers cannot understand words and sentences as humans can. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Mayer et al, for example, use an RDF schema to assist in labelling the quality standards of medical websites 27 . Another paper by Mayer et al describes a platform to automatically generate metadata descriptions that can be used to label the trustworthiness of the content of medical websites 28 . This metadata can be accessed through standard search engines, and the fact that the data are machine readable allows for more targeted querying, as well as potentially advancing interoperability.…”
Section: Discussionmentioning
confidence: 99%
“…Mayer et al, for example, use an RDF schema to assist in labelling the quality standards of medical websites 27 . Another paper by Mayer et al describes a platform to automatically generate metadata descriptions that can be used to label the trustworthiness of the content of medical websites 28 . This metadata can be accessed through standard search engines, and the fact that the data are machine readable allows for more targeted querying, as well as potentially advancing interoperability.…”
Section: Discussionmentioning
confidence: 99%
“…Another difficulty is choosing among dozens of guidelines [23,24]. These guidelines have been combined with automatic approaches that extract certain quality indicators [11,12,26-28] used for online health information retrieval. However, automatic approaches are still not widely used.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the AQUA system (Mayer et al, 2011) was designed to support the main tasks of the web content accreditation process, that is: identification of unlabeled resources having health-related content; visit and review of the identified resources; generation of content labels for the reviewed resources, and monitoring the labeled resources.…”
Section: Aqua System Overviewmentioning
confidence: 99%